Which types of mental health/substance misuse treatment services are available in primary care for adults in rural municipalities in Norway? - Hege Bruun; Anette Fosse; Birgit Abelsen (James Cook University, 2023)
Introduction: In Norway, the municipalities are responsible for providing primary health care, including mental health care. National rules, regulations and guidelines are the same throughout the country, but the municipalities can organise the service as they see fit. In rural areas, distance and time to specialised health care, recruitment and retention of professionals, and the care needs in the community will likely play a part in how the services are organised. There is a lack of knowledge of the variation of services, and which factors affect availability, capacity and organisation of mental health/substance-misuse treatment services for adults in rural municipalities.Aim: The aim of this study is to explore how mental health/substance-misuse treatment services in rural areas are organised and assigned, and which professionals provide the services.Methods: This study will be based on collected data from municipal plans and available statistic recourses on how the services are organised. These data will be contextualised with focused interviews with leaders in primary health care.Results: The study is ongoing. Results will be presented in June 2022.Discussion: Results from this descriptive study will be discussed in light of the development of mental health/substance-misuse health care with special focus on challenges and possibilities in rural areas.